Diagnostic Performance of High-Sensitivity Cardiac Troponin T Strategies and Clinical Variables in a Multisite US Cohort. Issue 17 (27th April 2021) - Allen, Brandon R.; Christenson, Robert H.; Cohen, Scott A.; Nowak, Richard; Wilkerson, R. Gentry; Mumma, Bryn; Madsen, Troy; McCord, James; Huis in't Veld, Maite; Massoomi, Michael; Stopyra, Jason P.; Montero, Cindy; et al.
Abstract : Background: European data support the use of low high-sensitivity troponin (hs-cTn) measurements or a 0/1-hour (0/1-h) algorithm for myocardial infarction to exclude major adverse cardiac events (MACEs) among patients in the emergency department with possible acute coronary syndrome. However, modest US data exist to validate these strategies. This study evaluated the diagnostic performance of an initial hs-cTnT measure below the limit of quantification (LOQ: 6 ng/L), a 0/1-h algorithm, and their combination with history, ECG, age, risk factors, and initial troponin (HEART) scores for excluding MACE in a multisite US cohort. Methods: A prospective cohort study was conducted at 8 US sites, enrolling adult patients in the emergency department with symptoms suggestive of acute coronary syndrome and without ST-elevation on ECG. Baseline and 1-hour blood samples were collected, and hs-cTnT (Roche; Basel, Switzerland) was measured. Treating providers blinded to hs-cTnT results prospectively calculated HEART scores. MACE (cardiac death, myocardial infarction, and coronary revascularization) at 30 days was adjudicated. The proportion of patients with initial hs-cTnT measures below the LOQ and risk according to a 0/1-h algorithm was determined. The negative predictive value (NPV) was calculated for both strategies when used alone or with a HEART score. Results: Among 1462 participants with initial hs-cTnT measures, 46.4% (678 of 1462) were women and 37.1% (542 of 1462) were Black with an age of 57.6±12.9 (mean±SD) years. MACEs at 30 days occurred in 14.4% (210 of 1462) of participants. Initial hs-cTnT measures below the LOQ occurred in 32.8% (479 of 1462), yielding an NPV of 98.3% (95% CI, 96.7–99.3) for 30-day MACEs. A low-risk HEART score with an initial hs-cTnT below the LOQ occurred in 20.1% (294 of 1462), yielding an NPV of 99.0% (95% CI, 97.0–99.8) for 30-day MACEs. A 0/1-h algorithm was complete in 1430 patients, ruling out 57.8% (826 of 1430) with an NPV of 97.2% (95% CI, 95.9–98.2) for 30-day MACEs. Adding a low HEART score to the 0/1-h algorithm ruled out 30.8% (441 of 1430) with an NPV of 98.4% (95% CI, 96.8–99.4) for 30-day MACEs. Conclusions: In a prospective multisite US cohort, an initial hs-cTnT below the LOQ combined with a low-risk HEART score has a 99% NPV for 30-day MACEs. The 0/1-h hs-cTnT algorithm did not achieve an NPV >99% for 30-day MACEs when used alone or with a HEART score. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02984436. Abstract : Supplemental Digital Content is available in the text.